2022
DOI: 10.1002/cam4.5528
|View full text |Cite
|
Sign up to set email alerts
|

Apoptin causes apoptosis in HepG‐2 cells via Ca2+ imbalance and activation of the mitochondrial apoptotic pathway

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…In the ectopic mouse models of HCC, tumor tissue growth was inhibited, DNA damage occurred in cells, and the levels of apoptotic proteins caspase- cells with apoptin for 72 h, 25% apoptosis was observed. The expression levels of cleaved-PARP and cleaved-caspase-3 were signi cantly higher, and the ROS levels in HepG-2 cells were signi cantly increased [22]. The above studies con rm the great potential and application value of apoptin in the treatment of HCC.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…In the ectopic mouse models of HCC, tumor tissue growth was inhibited, DNA damage occurred in cells, and the levels of apoptotic proteins caspase- cells with apoptin for 72 h, 25% apoptosis was observed. The expression levels of cleaved-PARP and cleaved-caspase-3 were signi cantly higher, and the ROS levels in HepG-2 cells were signi cantly increased [22]. The above studies con rm the great potential and application value of apoptin in the treatment of HCC.…”
Section: Discussionsupporting
confidence: 56%
“…Recent studies have identi ed apoptin as a protein precursor drug that is selectively activated in cancer cells through phosphorylation, thereby disrupting the cytoskeleton and promoting cell death [9]. It has also been found that apoptin induces apoptosis in HepG-2 cells via calcium ions, causing an imbalance and activating their mitochondrial apoptotic pathway [10]. The human immunode ciency virus (HIV) trans-activated transcription (TAT) protein, the rst cell-penetrating peptides discovered in 1998 [11], is derived from the human HIV viral TAT protein.…”
Section: Introductionmentioning
confidence: 99%
“…Calcium overload within mitochondria fails to maintain average mitochondrial membrane potential, leading to mitochondrial dysfunction. 23 Flow cytometry analysis revealed a significant increase in MMP in the Sur+Ru360 group compared with the Sur group and Sur+ saline group ( Figures 5E and F ). Surgery resulted in a decrease in mitochondrial membrane potential in hippocampal neurons ( Figures 5E and F ).…”
Section: Resultsmentioning
confidence: 92%
“…SARS-CoV-2 ORF 3a interferes with calcium homeostasis and induces autophagy to enhance viral infection ( Garrido-Huarte et al, 2023 ). Calcium imbalance triggers the mitochondrial apoptotic pathway to promote infection by chicken anemia virus ( Yu et al, 2023 ). Herpes simplex virus (HSV) infection induces a rapid increase in the intracellular calcium ion concentration, which plays a key role in facilitating virus entry ( Jiang et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%